Antimicrobial and Immunomodulatory Activities of Dried Extracts of Echinacea Purpurea - Bárbara Gonçalves de Oliveira; Luiz Filipe Ferreira Santos; Marliete Carvalho da Costa; Rafael Wesley Bastos; Paulo Henrique Fonseca do Carmo; Daniel de Assis Santos; Gérson Antônio Pianetti; Isabela Costa César (Universidade de São Paulo, 2023)
Abstract The use of Echinacea purpurea (EP), a plant native from North America, is widely diffused throughout the world, presenting many pharmacological applications, mainly for the treatment of infections of respiratory and urinary tracts. Due to the widespread commercialization of EP-based products, an effective evaluation of their pharmacological properties is essential to assure efficacy during clinical use. In this study, in vitro tests were performed to evaluate the antimicrobial activity of dried extracts of EP by the microdilution method. In addition, a phagocytosis model was employed to assess the immunomodulatory potential of the extracts. The increase in reactive oxygen species production, as well as the intracellular proliferation rate of Cryptococcus gatti after phagocytosis by macrophages in the presence of EP dried extracts were also evaluated. The analyzed samples showed no significant antibacterial activity; however, a slight antifungal activity was verified. Positive effects of EP extracts on the modulation of cellular immune response were observed in different experiments, indicating that this mechanism may contribute to the control and treatment of infections.